EFFECT OF DEGREE OF DEACETYLATION OF CHITOSAN ON CHEMICAL STRUCTURE AND COMPATIBILITY OF CHITOSAN/POLYAMIDE 6 BLENDS - Faridah Mohd Yusoh; Zainoha Zakaria (PERINTIS eJournal, 2021)
Solution blending technique was used to prepare chitosan/polyamide 6 (PA6) blends, where both compounds contain suitable functional groups that can be expected to promote compatibility between the polymers. Four types of chitosan with various degrees of deacetylation (DD) values were used to form chitosan/PA6 and the effect of DD of chitosan on the structure and compatibility of the blends were evaluated. Films of PA6, chitosan and chitosan/PA6 blends were employed to investigate the interaction between the polymers. Fourier Transform Infrared (FTIR) results of the blend showed the displacement of carbonyl band of amide group of chitosan to a smaller wavenumber implying the existence of strong hydrogen bonding between them. DSC analysis of the blend showed a reduction of melting point (Tm) and heat of enthalpy (ΔHm) due to the formation of new hydrogen bonds between the polymeric molecules. While, SEM analysis showed the disappearance of the smoothness surfaces of pure chitosan and gradually becoming undulating in the blends. The surface structure of blends are finer with increasing DD of chitosan indicating that there is effect of DD on the blends. Overall results showed that increasing the DD of chitosan increases the compatibility between chitosan and PA6 blend.